Biodiversity and stratification of dye plants in urban green spaces at Universitas Syiah Kuala, Banda Aceh, Indonesia - IQBAR IQBAR; NOVITA NOVITA (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Iqbar, Novita. 2026. Biodiversity and stratification of dye plants in urban green spaces at Universitas Syiah Kuala, Banda Aceh, Indonesia. Biodiversitas 27 (1): d270115.  https://doi.org/10.13057/biodiv/d270115. Urban green spaces are increasingly recognized for their role in conserving biodiversity and supporting cultural ecosystem services. This study presents the first systematic assessment of dye-producing plant diversity and ecological stratification within a university-based green open space, positioning the campus as a living laboratory for biocultural conservation and sustainable natural dye innovation. Floristic surveys recorded 32 dye-producing plant species from 18 families in the Green Open Space (GOS) of Universitas Syiah Kuala (USK), Indonesia, with Fabaceae and Asteraceae as the dominant families. Species richness, growth forms, pigment classes, and plant parts used for dye extraction were analyzed across canopy, understory, and groundcover strata. Statistical analyses revealed significant differences in species richness and species composition among vegetation strata (ANOVA, p<0.05), indicating pronounced vertical structuring of dye-producing plants. Trees dominated the canopy layer, providing long-term sources of pigments and associated ecosystem services. In contrast, understory and groundcover shrubs and herbaceous plants contributed rapidly renewable pigments suitable for small-scale extraction and educational applications. Flavonoids, tannins, and anthocyanins were the most prevalent pigment classes, generating a wide spectrum of natural colors. Compared with other urban ethnobotanical studies in Southeast Asia, dye-plant richness at USK was relatively high, reflecting spatial heterogeneity and the combined presence of native and ornamental species. Overall, this study demonstrates that urban academic landscapes can serve as living laboratories that integrate biodiversity conservation, ethnobotanical knowledge, and sustainable eco-textile education into multifunctional urban green-space management.